Bank Wakaf Mikro dan Strategi Baru Penguatan UMKM Berbasis Keuangan Inklusif - Muhammad Aladdin Hanif; Annisa Maulidia Alfian; Muhammad Zacky Dzulfikar; Darwanto Darwanto; Mochammad Ardani (Universitas Islam Lamongan, 2022)
The level of financial inclusion in Indonesia is 76,19%. It indicates that there are still many groups of people who have not received financial services. Economic empowerment and financial services at the micro level are easier and more accessible through microfinance institutions (MFIs). One of MFIs developed based on sharia principles is the Bank Wakaf Mikro (BWM). This study aims at improving the strategy for the role of BWM in financial inclusiveness and to support the economy from the MSME level. The method used is SWOT analysis by considering the internal and external factors that exist in BWM. The factors obtained through in-depth interviews with BWM leaders are processed quantitatively. The results show that BWM is still in the Stable Growth stage, because it has added value on weaknesses and opportunities. Strategies that can be implemented include collaborating with external agencies and simplifying regulations in BWM operations.